2007
DOI: 10.1523/jneurosci.1943-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

A Local Reduction in Cortical GABAergic Synapses after a Loss of Endogenous Brain-Derived Neurotrophic Factor, as Revealed by Single-Cell Gene Knock-Out Method

Abstract: To address questions of whether brain-derived neurotrophic factor (BDNF) released from active excitatory neurons acts locally only on GABAergic presynaptic terminals contacting these neurons or generally also on GABAergic terminals contacting other inactive neurons, we developed a single-cell gene knock-out method in organotypic slice culture of visual cortex of floxed BDNF transgenic mice. A biolistic transfection of Cre recombinase with green fluorescence protein (GFP) plasmids to layer II/III of the cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 62 publications
14
99
0
Order By: Relevance
“…Previous results have demonstrated that knockeddown BDNF expression in cultured cortical neurons decreases the number of GABAergic synapses, resulting in reduced mIPSC frequency (29). Overexpression of the BDNF gene, as well as chronic treatment with BDNF, promotes maturation of GABAergic innervations in the hippocampus (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results have demonstrated that knockeddown BDNF expression in cultured cortical neurons decreases the number of GABAergic synapses, resulting in reduced mIPSC frequency (29). Overexpression of the BDNF gene, as well as chronic treatment with BDNF, promotes maturation of GABAergic innervations in the hippocampus (17).…”
Section: Discussionmentioning
confidence: 99%
“…Although BDNF-TrkB signaling is known to regulate synaptic formation and transmission tone between glutamatergic principal neurons and interneurons (1)(2)(3)(4)11), its specific role in network function remains unclear. Using the TrkB-PV −/− mice, in which the trkB gene has been specifically deleted in PV+ interneurons, we show that BDNFTrkB signaling in PV+ interneurons is critical for the gamma band rhythmic activity in the hippocampal network.…”
Section: Discussionmentioning
confidence: 99%
“…Among cortical interneurons, PV+ interneurons express trkB abundantly (6). This anatomical organization of the BDNF signaling components and the known importance of feedback and feedforward communication between principal cells and interneurons (7)(8)(9)(10)(11) suggest a potential role for TrkB signaling in modulating neuronal network function.…”
mentioning
confidence: 88%
“…Evoked LFPs are dominated by excitatory synaptic transmission, but contain the combination of excitatory and inhibitory post-synaptic potentials. As chronic changes in BDNF signaling have been shown to positively correlate with the amount of perisomatic inhibition 6,25 by parvalbumin-expressing interneurons we also determined whether the TrkB.T1-EGFP transgenic animals showed changes in inhibitory inputs using immunohistochemistry. We examined the parvalbumin-positive boutons around pyramidal cell bodies, which provide the major source of inhibition in the cortex.…”
Section: Synaptic Efficacy Is Reduced By Overexpression Of Trkbt1mentioning
confidence: 99%
“…The reduction in excitatory transmission was thus larger than the response losses alone suggested. Chronic reduction of 9 postsynaptic release of BDNF is known to reduce perisomatic inhibition 25 . If this is mediated by a postsynaptic effect on inhibitory synapses, a similar mechanism could be at work in the transgenic mice.…”
Section: Normalization Model Reliably Matches Experimental Datamentioning
confidence: 99%